SPATIAL DISTRIBUTION OF ATTRIBUTES THE SURFACE LAYER OF A HAPLIC NITOSOL - VIEIRA, SIDNEY ROSA; CAMARGO, OTÁVIO ANTONIO DE; LIBARDI, PAULO LEONEL; ANDRADE, CRISTIANO ALBERTO DE; SIQUEIRA, GLÉCIO MACHADO (Revista Brasileira de Engenharia de Biossistemas, 2009)
The objective of this research was to study the spatial variability of some soil attributes from thesurface layer of a Haplic Nitosol. The experiment was conducted at the Escola Superior de AgriculturaLuiz de Queiroz in Piracicaba (SP, Brazil), on a plot of 0.625 ha divided into a regular grid of 5 m x 5m. The samples were collected at the 0.0-0.2 m depth. The attributes analyzed were: topography,texture (sand, silt and clay), pH in water, pH in KCl, total carbon (C), total nitrogen (N), exchangeablepotassium (K), exchangeable calcium (Ca), exchangeable magnesium (Mg), exchangeable acidity(Al), non-exchangeable acidity (H), total exchangeable bases (SB); cation exchange capacity (CEC),base saturation (V) and aluminum saturation (m). The data were analyzed using descriptive statisticsand geostatistical tools in order to interpolate data through the kriging technique for the constructionof maps. Exchangeable cations and potential acidity showed high variability. All variables showedspatial dependence, varying from moderate to strong. The average liming requirement (CN) was nota good measure of central tendency to represent the data population and thus was not sufficientlyrobust to adequately define the calcium application rate, because there was a significant amount ofregions demanding different rates than that recommended by the mean value.